2021
DOI: 10.1021/acs.jpclett.1c02915
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis and Structural Evolution of Colloidal Cesium Lead Halide–Lead Sulfide Heterostructure Nanocrystals for Optoelectronic Applications

Abstract: Heterostructures, combining perovskite nanocrystals (PNC) and chalcogenide quantum dots, could pave a path to optoelectronic device applications by enabling absorption in the near-infrared region, tailorable electronic properties, and stable crystal structures. Ideally, the heterostructure host material requires a similar lattice constant as the guest which is also constrained by the synthesis protocol and materials selectivity. Herein, we present an efficient one-pot hot-injection method to synthesize colloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 69 publications
1
23
0
Order By: Relevance
“…After the injection of the Cs precursor, PbSe NPs are consumed during the formation of CsPbBr 3 that grows epitaxially over the surface of PbSe. The epitaxial growth occurs due to the resemblance of the perovskite cubic crystal structure with the PbSe structure . In this process, the outermost Pb layer of CsPbBr 3 acts as the interface between CsPbBr 3 and PbSe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the injection of the Cs precursor, PbSe NPs are consumed during the formation of CsPbBr 3 that grows epitaxially over the surface of PbSe. The epitaxial growth occurs due to the resemblance of the perovskite cubic crystal structure with the PbSe structure . In this process, the outermost Pb layer of CsPbBr 3 acts as the interface between CsPbBr 3 and PbSe.…”
Section: Resultsmentioning
confidence: 99%
“…In recent times, designing heterostructures with suitable counterparts has been considered as an effective approach to passivate the surface defects and enhance the stability of LHPs. A few recent reports indicate the possibility of heterostructure formation of LHPs with lead chalcogenides because of their same cubic crystal structures with low lattice mismatch. , Lead chalcogenide NCs also act as the protecting layer of LHPs from humidity because of their hydrophobic nature, which enhances the stability of LHPs in an ambient environment. More recently, Rogach et al reported a facile strategy to design CsPbI 3 /PbSe nanoheterostructures (NHSs) using trioctyl phosphine (TOP)–selenium (Se) powder as the source of Se precursor . Furthermore, the Nripan and Zhang group synthesized heterostructures of CsPbX 3 (X: Cl, Br, I) with PbS using thioacetamide as the sulfur precursor. , These studies discuss the passivation of surface defects, tuning their electronic properties and enhancing the stability of perovskites. However, to the best of our knowledge, the effect of the size of lead chalcogenide on its optoelectronic properties is yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Tong et al improved the hot injection method, such as adding zeolite-encapsulated CsPbX 3 NCs, doping with Mn + , and in situ growth of CsPbX 3 NCs in metal-organic framework crystals, which improved the luminescence efficiency of the materials. 7,17,28,50–57 Zhang et al prepared dense and uniform CsPbX 3 thin films by thermal evaporation and applied them in lasers, LEDs, PSCs, and other photoelectric fields. 1,16,35,58–64 In recent years, electrospinning has emerged as a new method to prepare CsPbX 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, cesium lead halide (CPX 3 , X = Cl, Br, and I) perovskite quantum dots (PeQDs) have attracted a lot of attention due to the outstanding optical properties such as the large absorption coefficient, high quantum yields, emission peaks with narrow full width at half maximum (FWHM), and so on. , In addition, the ease of tuning the band gap via modulating the halide composition, thus shifting the single-peak emissive profiles from deep blue to red continuously, endows the materials with huge potential in wide applications such as displays, photovoltaics, optoelectronics, and so on. Meanwhile, lanthanide-doped upconversion nanoparticles (UCNPs), giving off anti-Stokes upconversion luminescence (UCL) under 980 nm NIR laser excitation, have demonstrated unparallel virtues against Stokes luminescence in various fields. However, unlike PeQDs, UCNPs critically rely on the dopants’ energy levels, with fixed UCL emissive peaks at certain wavelengths. Consequently, the UCL manipulation strategy has always been intensively focused over the decades.…”
Section: Introductionmentioning
confidence: 99%